2017
DOI: 10.1007/s13204-017-0608-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of titania nanotubes by anodizing of titanium in fluoride containing electrolytes

Abstract: Titania nanotubular structure was prepared by anodizing titanium metal in the fluoride containing electrolytes and studied for hydrogen reduction using photo electrochemical cell. Potentiodynamic scan was performed before actual anodizing to optimize the anodizing conditions. The morphology of the TiO 2 nanotubes was investigated by SEM and the presence of TiO 2 nanotubes was confirmed. Raman spectroscopy was done to confirm the different phases present. Hydrogen generation capability was revealed by electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…One of the pioneering efforts to utilize electrochemical anodization as an innovative approach for the surface modification of Ti-based alloys was performed by Dunn et al [ 221 , 222 ], where porous surface coatings are formed by anodization and incorporating antibiotics onto the oxide surface. Zwilling et al [ 223 ] also reported that anodization on Ti and Ti–6Al–4V alloys in the F − ion solution is an effective approach to attain tunable tubular oxide layers under different anodization conditions [ 16 , 17 , 65 , 133 , [224] , [225] , [226] , [227] , [228] , [229] , [230] , [231] , [232] , [233] , [234] , [235] , [236] , [237] , [238] , [239] , [240] , [241] , [242] , [243] , [244] , [245] , [246] , [247] , [248] , [249] , [250] , [251] , [252] , [253] , [254] , [255] , [256] , [257] , [258] , [259] , [260] , [261] , [262] ]. Since the Ti–6Al–4V alloy is a dual-phase alloy, the development kinetics of nanotubes are dissimilar for the α and β phases [ 69 ].…”
Section: Comparison Between Mono and Mixed Oxide Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the pioneering efforts to utilize electrochemical anodization as an innovative approach for the surface modification of Ti-based alloys was performed by Dunn et al [ 221 , 222 ], where porous surface coatings are formed by anodization and incorporating antibiotics onto the oxide surface. Zwilling et al [ 223 ] also reported that anodization on Ti and Ti–6Al–4V alloys in the F − ion solution is an effective approach to attain tunable tubular oxide layers under different anodization conditions [ 16 , 17 , 65 , 133 , [224] , [225] , [226] , [227] , [228] , [229] , [230] , [231] , [232] , [233] , [234] , [235] , [236] , [237] , [238] , [239] , [240] , [241] , [242] , [243] , [244] , [245] , [246] , [247] , [248] , [249] , [250] , [251] , [252] , [253] , [254] , [255] , [256] , [257] , [258] , [259] , [260] , [261] , [262] ]. Since the Ti–6Al–4V alloy is a dual-phase alloy, the development kinetics of nanotubes are dissimilar for the α and β phases [ 69 ].…”
Section: Comparison Between Mono and Mixed Oxide Nanotubesmentioning
confidence: 99%
“…This study also highlighted that the diameters of the nanotubes can only be modified from 88.5 to 122.9 nm using various concentrations of electrolyte from 1 wt% NH4F + 20 wt% H2O to 1 wt% NH4F + 30 wt% H2O at 20 V, respectively [ 263 ]. Extensive research has been conducted in the field of nanotubes production on Ti-based alloys, especially the Ti–6Al–4V alloy in the last decade; whereby useful information is available on the impact of anodization on the features of MONs in this system [ 16 , 17 , 65 , 133 , [224] , [262] ]. One of the most comprehensive studies in this field was performed by Li et al [ 254 ], where they explored the thermal constancy and in vitro bioactivity of nanostructured Ti–Al–V–O formed on Ti–6Al–4V.…”
Section: Comparison Between Mono and Mixed Oxide Nanotubesmentioning
confidence: 99%
“…Anodization offers the additional advantages of simplicity, and ease of fabrication and scaling-up. The tube diameter, length and wall thickness can be properly manipulated by processing parameters including electrolyte composition, applied voltage, pH, temperature, and time [221]. In general, the applied voltage regulates the nanotube diameter, and the anodizing time controls the tube length.…”
Section: Electrochemical Anodizationmentioning
confidence: 99%
“…Nanomaterials 2020, 10, x FOR PEER REVIEW 15 of 57 electrolyte composition, applied voltage, pH, temperature, and time [221]. In general, the applied voltage regulates the nanotube diameter, and the anodizing time controls the tube length.…”
Section: Electrochemical Anodizationmentioning
confidence: 99%
“…To improve the stability of SnO 2 −Sb electrode, an interlayer, acting as a binder between the Ti and SnO 2 −Sb phases, was introduced through a thermal oxidation followed by an electrochemical reduction process ,. With the continuous development on the preparation method for TiO 2 −NTs, the feasibility research of TiO 2 −NTs to be used as support for catalyst has attracted more and more attention . A novel Sb‐doped SnO 2 electrode was constructed by designing and regenerating the microstructure of the Ti substrate ,.…”
Section: Introductionmentioning
confidence: 99%